Angels on the edge of the world: geography, literature, and English community, 1000 - 1534 - Lavezzo, Kathy (Cornell paperbacks, 2006)
Introduction : modern motherland and ancient otherworld -- Another country : Ælfric and the production of English identity -- Gerald de Barri and the geography of Ireland's conquest -- Locating England in the Polychronicon -- Beyond Rome : mapping gender and justice in the Man of Law's tale -- "From the very ends of the earth" : medieval geography and Wolsey's processions